Customary Arbitration In Nigeria: A Review Of Extant Judicial Parameters And The Need For Paradigm Shift - Akanbi, Muhammed Mustapha; Abdulrauf, Lukman Adebisi; Daibu, Abdulrazaq Adelodun (Journal of Sustainable Development Law and Policy, 2025)
Two forms of arbitration exist in present-day Nigeria; the first is indigenous to the various communities in the country and it is determined by the customs and traditions of the individual community. The second, which was imported, derives its source from the general laws and practice of England. The latter, which is arguably, alien to the culture and tradition of traditional Nigerian communities, has often been superimposed and applied by courts. The continuing subjugation of customary arbitration can be seen in the attitude of the Nigerian courts, whereby reliance is placed on the parameters of modern arbitration in the determination of a valid customary arbitration award in Nigeria. This article contends that the attitudes of courts in the determination of the binding nature of an award given under customary arbitration, using the parameters of modern arbitration, has caused considerable damage to the essence and potency of customary arbitration practice in Nigeria. In order to be authentic, it is contended that judicial development of customary arbitration, must respond to the traditions, attitudes and goals of the people whose society is under consideration. It should not be subject to a validity test by reference to orthodox arbitration or arbitration under the received English law. Consequently, the article examines the extant parameters to which the Nigerian courts subject the characteristics of customary arbitration in Nigeria. The article discusses the need for a paradigm shift in order for customary arbitration to respond to the exigencies of customs.